A Study on Integrated Use of Turbulence Theory and Multi-Frame Leadership in School Leadership and Change - Cheng-Hung Chen (National Taipei University of Education, 2014)
This study aimed to engage in an empirical investigation on school leaders' comprehensive perspectives of adopting both turbulence theory and multi-frame leadership model on change and leadership within school settings. Applying the qualitative case study approach, workshops and focus group interviews were held involving five directors and three principals from different elementary schools, who graduated from the master program in school administration where the researcher serves, to discuss and reflect upon the cross match of two theories as they may be applied to change and leadership. Accordingly, both theories' practical application encompassed three advantages: "both theories interactively match with each other," "both theories correspond to the authentic context of school leadership and change," and "the matching matrix of both theories could serve as school leaders' decision check list;" meanwhile, there were two issues that needed to be noticed and examined, including "the differentiation, definition and measurement of turbulence levels," and "the subjective identification of turbulence levels." This study concluded by proposing practical implications of applying theory into practice of school leadership and change.